Study on the sound absorption characteristics and noise reduction mechanism of coconut-shell-activated carbon particles and coconut fiber composite biomass sound-absorption materials - Zhenhua Hou; Xiaoying Ma; Liai Pan; Rui Zhang; Libo Wang (Materials Research Express)
Sound-absorbing materials are widely used in the field of automotive industry. Biomass materials are abundant in the nature, some of which have natural sound absorption and noise reduction properties. Biomass sound-absorption materials are green and pollution-free, which have obvious noise reduction effect on middle- and high-frequency noises, a large specific surface area, a light weight and strong sound absorption effect. The purpose of this paper is to prepare new types of biomass composite sound absorbing material. In order to analyze the sound absorption and physical properties of biomass sound-absorbing materials, the noise reduction performance of different structures of biomass sound-absorbing materials was analyzed. In this paper, the biomass sound-absorbing materials coconut-fiber- and coconut-shell-activated carbon particles were used to make samples. A coconut-shell-activated carbon sound-absorption material (CSAC) was made. The cylindrical holes were made and filled with coconut fiber materials to form composite sound-absorbing materials (CSAC-F). The acoustic performance of an impedance tube was tested based on the acoustic absorption coefficient, whose physical performance was studied by means of a scanning electron microscope (SEM), Brunauer, Emmett and Teller (BET), x-ray diffraction (XRD), a Fourier transform infrared spectrometer (FTIR), thermogravimetric analyzer (TGA) and other detection methods. In contrast, the sound absorption effect of CSAC-F was better in the middle- and low-frequency range, whose microstructure was analyzed and its mechanism of noise reduction was studied. This study will provide a new way for the research and development of sound-absorbing materials in the automotive industry, and biomass sound-absorbing materials have potential applications in the noise absorption and vibration control of automotive interior.